Impact of mental fatigue on tennis players’ attention and groundstroke performance - Öztürker, Cenk; Şahan, Asuman; Erman, Kemal Alparslan (Frontiers in Psychology, 2025)
ObjectivesThis study aimed to determine the effects of mental fatigue on attention and groundstroke targeting performance in tennis players.MethodsA total of 66 young male tennis players (age: 24.32 ± 2.46 years) participated in this randomized placebo-controlled crossover trial. Interventions included mental fatigue (MF), non-fatiguing effect (Placebo), and no mental fatigue (Control). The Stroop Attention Test (SAT) and Tennis Groundstroke Targeting Test (TGTT) depth and accuracy sections were administered before and after all interventions. Changes over time in normally distributed homogeneous data were determined using repeated-measures ANOVA (3×2), with Bonferroni correction applied for p-values for normally distributed variables and the Friedman test for non-normally distributed variables. Paired samples t-test and Wilcoxon test were used for pairwise comparisons of normally and non-normally distributed data, respectively.ResultsPost-test pairwise comparisons showed that the MF intervention significantly increased SAT completion times and SAT error scores (p < 0.001). Post-intervention TGTT scores showed significant differences between MF, Placebo, and Control (p < 0.001), with post hoc analysis indicating that TGTT scores were significantly lower in the MF intervention compared to Control and Placebo (p < 0.001).ConclusionThis study demonstrates that acute mental fatigue decreases attention and tennis groundstroke targeting performance in male tennis players.